Etiology and characteristics of community-acquired pneumonia in an influenza epidemic period. (June 2019) - Lin, Chun; Chen, Huanzhu; He, Ping; Li, Yazhen; Ke, Changwen; Jiao, Xiaoyang
Highlights: 1 Not all patients (only 123(63.08%)) have definitely pathogens found. 2 Non-influenza patients' co-infection were more common in the peak of Influenza. 3 The pattern of co-infection in our study is different from previous study. 4 Yeast, Acinetobacter baumannii and Klebsiella pneumoniae have high positive rate. Abstract: Purpose: The etiology of community-acquired pneumonia (CAP) in hospital patients is often ambiguous due to the limited pathogen detection. Lack of a microbiological diagnosis impairs precision treatment in CAP. Methods: Specimens collected from the lower respiratory tract of 195 CAP patients, viruses were measured by the Single-plex real-time PCR assay and the conventional culture method was exploited for bacteria. Results: Among the 195 patients, there were 46 (23.59%) pure bacterial infections, 20 (10.26%) yeast infections, 32 (16.41%) pure viral infections, 8 (4.10%) viral- yeast co-infections, and 17 (8.72%) viral-bacterial co-infections. The two most abundant bacteria were Acinetobacter baumannii and klebsiella pneumoniae, whereas the most common virus was influenza A. Conclusions: Non-influenza respiratory microorganisms frequently co-circulated during the epidemic peaks of influenza, which easily being ignored in CAP therapy. In patients with bacterial and viral co-infections, identifying the etiologic agent is crucial for patient's therapy.